Synthesis of novel thermotropic liquid crystalline polymers by a reactive extrusion process - Oh, Kyunghwan; Kim, Hoyeon; Seo, Yongsok (RSC advances, 2019)
The syntheses of new thermotropic liquid crystalline polymers (TLCPs) were carried out via the polyaddition reactions of diepoxy-containing mesogens and a monoamine (1-naphthylamine). Both bulk polymerization and reactive extrusion were tested. The reaction between the two epoxy rings on the mesogen unit and the primary amine produces a thermotropic liquid crystalline polymer in the extruder. The amine group combines with the two epoxy rings in a single step via a polyaddition reaction to produce thermotropic liquid crystalline polymers without the formation of any by-products. Both polymers were found to exhibit nematic mesophase characteristics, which were examined by using polarized optical microscopy. The new thermotropic liquid crystalline polymers obtained with the bulk reaction have high molecular weights, whereas the polymers synthesized by using reactive extrusion have low molar mass due to their short residence times in the extruder. All the synthesized TLCPs were found to exhibit high thermal stability. Their decomposition temperatures were found to be above 350 °C, but their melting temperatures are low (below 250 °C). The liquid crystalline structures of the TLCPs were verified by performing 2D X-ray diffraction measurements. Scanning electron micrographs of the drawn polymer fibers show that the orientation of their morphologies lies predominantly along the direction of the fibers. The polymers synthesized with the reactive extrusion process have the same physical properties as those obtained with the bulk polyaddition reaction. This observation demonstrates the feasibility of the mass production of new TLCPs through reactive extrusion. The syntheses of new thermotropic liquid crystalline polymers (TLCPs) were carried out via the polyaddition reactions of diepoxy-containing mesogens and a monoamine (1-naphthylamine).